The EFEKTIFITAS MODEL MULTILITERASI BERBANTUAN EDPUZZLE UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SD : EFEKTIFITAS MODEL MULTILITERASI BERBANTUAN EDPUZZLE UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SD - Rahmasari, Melati Ulya Nur; Sukasih, Sri (Jurnal Gentala Pendidikan Dasar, 2025)
The lack of pre-reading and post-reading activities leads to low reading comprehension skills among students. The application model and media can be a solution to this problem. The purpose of this study is to analyse the effectiveness of the multiliteracy model supported by edpuzzle in improving the reading comprehension skills of fifth grade students. The material taught focuses on reading comprehension skills in expository text learning with quantitative methods, quasi-experimental design. The sample of this study consisted of an experimental class and a control class of 21 students each. The data collection techniques used are test and non-test techniques, which are then analysed by normality test, paired sample t-test and N-gain test. There is a significant difference in the paired sample t-test with a sig value. (2-tailed) <0.001<0.05. Based on the N-gain test, it was found that the average learning scores in the experimental class were higher than in the control class, with scores of 61.47% and 42.07% respectively. Thus, it can be concluded that the multiliteracy model supported by Edpuzzle is more effective in improving the reading comprehension skills of fifth grade students of SDN Karanganyar 01 Semarang City on expository text material compared to conventional methods